2008
DOI: 10.1371/journal.pone.0003919
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals in Healthy Adult Ugandan Blood Donors and Their Impact on Conducting International Vaccine Trials

Abstract: BackgroundClinical trials are increasingly being conducted internationally. In order to ensure enrollment of healthy participants and proper safety evaluation of vaccine candidates, established reference intervals for clinical tests are required in the target population.Methodology/Principal FindingsWe report a reference range study conducted in Ugandan adult blood bank donors establishing reference intervals for hematology and clinical chemistry parameters. Several differences were observed when compared to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

54
115
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(180 citation statements)
references
References 13 publications
54
115
11
Order By: Relevance
“…Similar findings were noted in Rwanda [8]. Sex differences in UA have been previously documented by Roche Diagnostics, Eller et al, Saathoff et al and Khan et al [2,4,5,9] which could be due to the influence of sex hormones resulting in differences in body mass between sexes. The general absence of sex differences for BUN, CA, and PHOS in this study agrees with those reported in the reagent manufacturer's reference range values [2]; the result is similar to studies done in Pakistan [10], an indication that these parameters are not influenced by sex hormones.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Similar findings were noted in Rwanda [8]. Sex differences in UA have been previously documented by Roche Diagnostics, Eller et al, Saathoff et al and Khan et al [2,4,5,9] which could be due to the influence of sex hormones resulting in differences in body mass between sexes. The general absence of sex differences for BUN, CA, and PHOS in this study agrees with those reported in the reagent manufacturer's reference range values [2]; the result is similar to studies done in Pakistan [10], an indication that these parameters are not influenced by sex hormones.…”
Section: Discussionsupporting
confidence: 85%
“…Male creatinine values for the current study were lower than those for America, Kericho and Kuwait groups [2,5,11], greater than those for Tanzanian population [3] and comparable with those of the Uganda group [4]. North Rift female creatinine values were higher than the America, Mbeya, and Kampala [2][3][4] but lower than those for Kericho populations [5]. Among the electrolytes, NA and [4,13].…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations